UK–EU law enforcement cooperation post-Brexit: A UK law enforcement practitioner perspective - Shellaker, Matthew (Criminology & criminal justice, 2024)
Law enforcement cooperation between the United Kingdom and the European Union has experienced substantial change. The practice and impact of police cooperation are aligned with various formal and informal arrangements previously based on a European framework, policy, legislation and process. Following Brexit, the United Kingdom became detached from some of these arrangements. Opposing sides of the Brexit debate argued that the implications of the United Kingdom leaving the European Union would result in outcomes ranging from improved police cooperation to fundamental damage to law enforcement combating cross-border and organised crime. While it is acknowledged that more change will occur in the policy and legislative framework that governs police cooperation between the United Kingdom and the European Union, this article explores the current situation from the perspective of interview accounts from police practitioners (n = 14) and academics (n = 3) working in the field. This article applied ‘nodes of governance’ to police cooperation between the United Kingdom and European Union. This article demonstrates a range of issues that have impeded the ability of the United Kingdom to work with its former partners. At the same time, good police relations remain, and informal police cooperation continues.